Think Pair Share (TPS) Learning Methods to Improve Student Learning Activities - Endang, Endang Suprihatin; Siswandari; Suharno; Jumintono (Jurnal Pedagogi dan Pembelajaran, 2023)
Active learning plays a vital role in learning because it can affect student learning outcomes. However, teachers still use conventional learning methods or teacher-centered learning. This study aimed to analyze the increase in student activity, student response, and student learning outcomes using the Think Pair Share (TPS) learning method. This type of research is a pre-experimental design with a one-group pretest-posttest design. The sample in this study was 35 students. Data collection methods used observation, tests, and questionnaires with instruments including student activity observation sheets, pre-test, and post-test questions, and student response questionnaire sheets. Data were analyzed using a quantitative descriptive method. Based on the research results, the results of student learning activities showed a percentage of 78% at meeting 1 increased to 84.64% at meeting 2. The TPS learning method received very good responses from students. A percentage of 81.56% indicated this. Student learning outcomes in the pre-test by 31% increased to 100% in the post-test results. Applying the TPS learning method could increase student activity, response, and learning outcomes in vocational fashion subjects.